Designing landscapes of affordances for ageing in place - O. Söderström; T. Zittoun; F. Gfeller; A. Ruggeri; I. Kloepper (Geographica Helvetica)
This paper aims to contribute theoretically, methodologically, and empirically to research and interventions regarding ageing in place. Theoretically, the paper contributes by drawing on the literature on landscapes of care and landscapes of affordances to suggest a multiscalar and more-than-human approach to ageing in place. Methodologically, we argue that studying ageing in place requires a participatory and translational methodology. Participatory methods are, on one hand, a prerequisite for an understanding of how older adults live their daily lives and particularly use a “landscape of affordances” in their social and material environment. A translational process, on the other hand, is necessary to elaborate research results incrementally across the different stages that lead to interventions on the ground. Finally, empirically, we draw on results of a study based on go-along interviews, photographic observations, and biographic interviews. In its empirical part, our paper describes the difficulties and gains of the different aspects of this participatory and translational process. In summary, the paper both develops the conceptual underpinnings of “ageing in place” and informs the methodologies of applied research in this domain.